Autologous blood extracellular vesicles and specific CD4+ T-cell co-activation - Neyrinck-Leglantier, Déborah; Tamagne, Marie; L’honoré, Sasha; Cagnet, Léonie; Pakdaman, Sadaf; Marchand, Alexandre; Pirenne, France; Vingert, BenoÎt (Frontiers in Immunology, 2022)
Extracellular vesicles (EVs), which are generated by cell membrane budding in diverse cells, are present in variable numbers in the blood. An immunoregulatory role has been demonstrated principally for heterologous EVs, but the function of the EVs present naturally in blood remains unknown. We hypothesize that these autologous EVs might also modulate the phenotype and function of immune system cells, especially CD4+ T lymphocytes (TLs), as previously described for heterologous EVs. Several membranes and soluble immunoregulatory molecules were studied after the treatment of CD4+ TLs with autologous EVs. No direct activation was detected with autologous EVs, contrasting with the findings for heterologous EVs. However, following treatment with autologous EVs, a soluble form of CD27 (sCD27) was detected. sCD27 is strongly associated with lymphoproliferation. Autologous EVs have been shown to increase TL proliferation only after T-cell receptor (TcR) engagement due to polyclonal or specific-antigen stimulation. Our results therefore suggest that the EVs present in the blood have an immunomodulatory role different from that of heterologous EVs. These findings should be taken into account in future studies, particularly those focusing on infectious diseases, autotransfusion or doping practices.